Efficacy of sub-occipital muscles decompression techniques in restoring functional walking capacity in hemiplegic cerebral palsy children - Azam, Ahmed M. (International Journal of Contemporary Pediatrics, 2017)
Background: This work was carried out to investigate the efficacy of sub-occipital muscles decompression in restoring functional walking capacity in hemiplegic cerebral palsy children. Methods: Thirty children were enrolled in this study and randomly assigned into two groups; group A (sub-occipital muscles decompression techniques plus traditional physiotherapy program) and group B (Traditional physiotherapy program only). 6 minutes walking test (6MWT) was used to quantify, evaluate and follow functional walking capacity also flexibility tests were used to detect and follow hamestring and calf muscles elasticity. This measurement was taken before treatment and after 12 weeks of treatment for all patients. The children parents in both groups A and B were instructed to complete 3 hours of home routine program. Results: Data analysis was available on the 30 hemiplegic cerebral palsy children participated in the study. No significant difference was recorded between the mean values of all parameter of the two groups before treatment. By comparison of the two groups ’results after treatment there was significant improvement in functional walking capacity in favor of the study group. The difference between pre-and post-treatment results of each group was significant. Conclusions: According to the results of this study supported by the relevant literature it can be concluded that the combined effect of physiotherapy training program in addition to sub-occipital muscles decompression techniques can be recommended in restoring functional walking capacity in hemiplegic cerebral palsy children.